The American atom: A documentary history of nuclear policies from the discovery of fission to the President 1939-1984 (Univ. of Pennsylvania, 1984)
The book presents the first comprehensive collection of primary documents which tell the story of atomic energy in the United States from discovery of fission through the development of nuclear weapons, international proliferation, and attempts at control. This book also examines carefully the Mahattan Project, the Oppenheimer Case, the hydrogen, bomb, nuclear testing and the test ban, proliferation, arms control, and the startegy of deterrence